EFEKTIVITAS GERAKAN LITERASI MEMBACA TERHADAP PENINGKATAN PRESTASI HASIL BELAJAR - Muji Zain Naufal; Hasanudin, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Quality education is an important indicator in improving insight and knowledge. Therefore, the enhancement of reading literacy needs to be carried out in a well-planned and sustainable manner so that, in the future, reading literacy becomes a culture, particularly among students and Indonesian society in general. This study aims to determine the effectiveness of the reading literacy movement in improving academic achievement. The research method used is an experimental method. The participants in this study were 35 tenth-grade students at SMA Nahdlatul Ulama Kaplongan Indramayu, selected using a saturated sampling technique. The results showed an increase in students’ academic achievement after the implementation of the reading literacy program, with an average improvement of 17.6%. It can be concluded that the reading literacy movement is effective in improving students’ academic achievement.